Investors’ Awareness, Perceived Risk Attitudes, and Behavior in the Nepalese Capital Market - Subedi, Santosh (JMC Research Journal, 2025)
This study examines investors’ awareness, risk attitudes, and behavior in the Nepalese capital market, focusing on individual investors’ perceptions. A descriptive research design was employed to provide a comprehensive analysis, using a deductive and quantitative approach. Primary data were collected through questionnaires and analyzed using descriptive statistics, with mode calculations for key responses. Findings indicate that most investors possess moderate knowledge of the capital market and rely on fundamental analysis. Awareness of mutual funds, central depository system (CDS), credit rating agencies, and portfolio management services were prevalent. Investors perceive good news as positively impacting the market, bad news as negative, and informational news as inconsistent. Political and economic changes are major factors influencing investment decisions, while market trends significantly affect investor behavior. A key challenge identified is the lack of investor confidence. Additionally, most investors assess risk and return before investing, preferring moderate risk with moderate returns. They view stock market returns as attractive as riskier as other investments. Government regulations are deemed insufficient in safeguarding investments. Regression analysis reveals that investor behavior is positively linked to awareness, risk perception, social learning, financial literacy, and cognitive-affective factors.